A review of illicit psychoactive drug use in elective surgery patients: Detection, effects, and policy. (December 2017) - Selvaggi, Gennaro; Spagnolo, Antonio G.; Elander, Anna
Abstract: Limited information is present in literature regarding detection of illicit drug users visiting physicians when planning elective surgery; also, there is no update manuscript that is illustrating the effects of illicit drugs use that require reconstructive surgery interventions. Aims of this manuscript are: 1) to summarize existing knowledge, and give surgeons information how to detect patients who might possible use illicit drugs; 2) to review the effects of illicit drug use that specifically require reconstructive surgery interventions; 3) to assess on existing policies on asymptomatic illicit drug users when planning elective surgery. Studies were identified by searching systematically in the electronic databases PubMed, Medline, The Cochrane Library and SveMed+. Because of the nature of research questions to be investigated (drug policy and surgery), a "systematic review" was not possible. In spite of some existing policies to detect illicit drug use in specific situations such as workplaces or acute trauma patients, there is a lack of data and lack of information, and subsequently no policy has ever been made, for detection and management of illicit drug use asymptomatic patients requesting or referred for plastic surgery interventions. This manuscript poses questions for further ethical evaluations and future policy. Highlights: This manuscript give surgeons information how to detect patients who might use illicit drugs. It reviews the effects of illicit drug use that specifically requires reconstructive surgery interventions. Existing policies on asymptomatic illicit drug users seeking for any elective surgery are reviewed.